A THE EFFECT OF USING THE TIKTOK APPLICATION ON THE MORALS OF CLASS VIII STUDENTS AT MUHAMMADIYAH 7 COLOMADU JUNIOR HIGH SCHOOL KARANGANYAR IN THE 2023/2024 ACADEMIC YEAR - Amanda Afnan Fisara; Suhadi Suhadi; Yetty Faridatul Ulfah (Sean Institute, 2023)
The type of research used in research at SMP Muhammadiyah 7 Colomadu, Karanganyar is a quantitative correlation approach. The population in this study was class VIII students at SMP Muhammadiyah 7 Colomadu Karanganyar with a sample of 50 students taken using simple random sampling technique. This research uses data collection techniques, namely questionnaires. Data analysis techniques in research use simple linear analysis and hypothesis testing (T test, F test. Correlation coefficient test). This research shows the results of 1) The use of social media Tik Tok among students at SMP Muhammadiyah 7 Colomadu. Results were obtained in the high category of 20.0% or 10 students, the medium category of 70.0% or 35 students, and the low category of 10.0% or 5 students. 2) Student morals at SMP Muhammadiyah 7 Colomadu, from each suspension the results were obtained in the high category of 12% or 6 students, the medium category of 78.0% or 39 students, and the low category of 10% or 5 students. 3) This research shows that the influence of using social media TikTok has an influence on the morals of students at SMP Muhammadiyah 7 Colomadu. This is based on the results of the SPSS table output, where the significance level is P-value (0.000) < Sig (0.05), then Ho is rejected and Ha is accepted, which means